Ti(C, N)-based cermet with different TaC/(TaC+WC) weight ratio by in-situ reactive hot pressing: Microstructure and mechanical properties. (December 2020) - Zhao, Xianrui; Zhang, Mengxian; Zuo, Dunwen; Fang, Yihang; Zhang, Qiangyong; Zhu, Zhengyu; Liu, Guixiang; Xu, Feng
Graphical abstract: Abstract: To further improve the mechanical properties of the Ti(C, N)-TiB2 -Co cermets prepared by in-situ reaction hot pressing, the TaC and WC were added in Ti-C-BN-Co system. The effect of varying TaC/(TaC + WC) weight ratio on the microstructure and mechanical properties of the cermets was studied by scanning electron microscope, X-ray diffraction, and tests of Vickers hardness, bending strength, and fracture toughness. The result demonstrated that, as the TaC/(TaC + WC) weight ratio increased, the CoW2 B2 impurities phase gradually decreased until it disappeared. The main peak ((200)) of Ti(C, N) gradually shifted to the left and the lattice parameters increased. Microstructure analyses of cermets revealed that the porosity increased first and then decreased. The so-fabricated cermets contained three kinds of core-ring structure grains: black core-gray ring, dark gray core-gray ring, and dark gray core-white inner ring with a gray outer ring. As the TaC/(TaC + WC) weight ratio increased, the thickness of the ring phase gradually increased. The Vickers hardness, bending strength, and fracture toughness of the cermets first increase to the maximum and then decrease; when the weight ratio was 0.4, the maximum values were 2052 HV10, 998 MPa, and 7.68 MPa·m 1/2, respectively.